Epidemiological Survey On The Infection With Hydatid Cysts In Sheep In AL- Anbar Province: M.K.Abbass , Y.B.Ridah - Abbass, M. K. (The Iraqi Journal of Veterinary Medicine, 2007)
Survey on the distribution of Hydatiddosis in sheep in A Anbar province havebeen done during period 1/1/2OO2to31/12/2002. This survey showed that℅28.29 of sheep suffering from Hydatidosis also showed that the infection ismore in female than in male .The incidence was increased in cold season,meanwhile the percentage of organ infection in both male & female being low inliver but higher in lung and the infection the highest in organs, liver and lungtogether.